LEGAL ASPECTS OF DEVELOPMENT OF ORGANIC AGRICULTURE IN UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION - Ignatenko, Iryna (Economics of Agriculture, 2020)
In modern economic conditions, organic production is gaining global significance, partly addressing food security and contributing to the well-being of the population. Ukraine is in the top-20 of world leaders in the organic movement. In this regard, the prospects for the development of organic farming are considered. The current state of regulatory support for organic production in Ukraine has been analyzed. It is proposed to approve the procedure for certification of organic production, the procedure and requirements for labeling of organic products, as well as requirements for material and technical base and other infrastructure necessary to perform functions of certification of organic production and circulation of organic products. The necessity of approving the criteria for determining the suitability of agricultural lands for use in the process of organic production is substantiated.